Influence of Substrate Temperature and Directness of Approach on the Escape Responses of Juvenile Collared Lizards - Braun, Cody A.; Baird, Troy A.; LeBeau, Jennifer K. (Herpetologica, 2010)
Escape theory is a well-known conceptual framework proposed to predict adaptive behavior patterns of free-ranging prey animals with respect to predator avoidance. Escape-theory models are based on the premise that prey should adopt behavior that balances predation risk incurred by remaining in a chosen location against the cumulative fitness costs resulting from fleeing such locations. Ectotherms are expected to be more vulnerable when their locomotory abilities are diminished at lower ambient temperatures, and risk to prey is expected to increase with the intensity of threat posed by potential predators. We conducted field experiments involving approach by a simulated predator (a human observer) to test both the influence of substrate temperature and the intensity of threat on escape behavior in free-ranging juvenile collared lizards, Crotaphytus collaris. As predicted by theory, flight initiation distance was negatively correlated with substrate temperature. Our results also supported the prediction that the intensity of juvenile responses should increase with perceived threat intensity. Juveniles fled or hid in more trials when they were approached directly; direct approach resulted in subjects responding when the predator stimulus was farther away, and for trials in which hatchlings fled, they moved farther when approached directly. Taken together, our results indicate that juvenile collared lizards alter their behavior with respect to increased risk in a manner that is consistent with the predictions of contemporary escape theory.